PENGARUH KOREAN WAVE SEBAGAI INSTRUMEN DIPLOMASI PUBLIK KOREA SELATAN TERHADAP MINAT ANGGOTA KOMUNITAS SAHABAT KOREA MEMILIH BEASISWA GLOBAL KOREA SCHOLARSHIP (GKS) - Nabila Fahri Adha (2022)
This study aims to analyze the influence of public diplomacy efforts carried out by South Korea through the Korean Wave on the interest of members of the Korean Friends community in choosing the Global Korea Scholarship (GKS). The theory tested in this study is the theory of public diplomacy by Mark Leonard. The method used is a quantitative description with the type of survey that aims to obtain the results of community members' answers through the distribution of questionnaires with a research sample of 78 respondents. The data analysis technique used in this research is Multiple Linear Regression Analysis. The results of the study found that the sub-variables of public diplomacy consisting of News Management (X1), Strategic Communication (X2) and Relationship Building (X3) had a significant effect on the interest of Sahabat Korea members in choosing the GKS scholarship. However, in this study, News Management conducted by the South Korean government did not get good enough results to influence interest in choosing the GKS scholarship. While the Strategic Communication sub-variable is the dominant factor that significantly influences the interest of Sahabat Korea members to choose the GKS scholarship. Keywords: Public Diplomacy, Korean Wave, Indonesia, South Korea, GKS